Wild bee diversity in two sites of tropical dry forest in central Mexico - Concepción Martínez-Peralta; Hugo E. Fierros-López; Karina Sánchez-Echeverría; Israel Valencia-Esquivel; Karla M. Aguilar-Dorantes (Journal of Hymenoptera Research)
Bee communities are strongly dependent on the floral resources provided by vegetation; hence, factors that affect floral availability also affect bee communities. In this study, we compare bee diversity and seasonality between two localities in the Tropical Dry Forest (TDF) of central Mexico. We quantified the vegetation cover at each locality using satellite imagery and compared it between localities using linear models. At each locality, we sampled wild bees over one year, covering two rainy seasons and one dry season. Bees were sampled using entomological nets, focusing on understory vegetation. Association of bee abundance with each season and locality was tested using a chi-squared test. Diversity was estimated using Hill numbers, and species composition was analyzed using non-metric multidimensional scaling. Diversity and composition were compared across localities and seasons. We collected 1,076 bees of 148 species, 55 genera, and five families. The most abundant families were Apidae and Megachilidae. There were no significant differences between sites in the diversity of any of the orders. The diversity of the three orders was significantly higher at both localities during the 2015 rainy season. Our results indicate that Mexican TDF is rich in bee species. However, the differences in community composition between localities and the current deforestation rate of these habitats imposes challenges to effectively preserve bees in the tropical dry forest.